Exploring the thermoluminescent characteristics of nano α-Al2O3: Influence of heating rate on glow peaks and activation energy - Mammadov, Sahib; Gurbanov, Muslim; Ahadov, Ahmad (European Journal of Chemistry, 2024)
The thermoluminescence (TL) characteristics of nano α-Al2O3 (40 nm) under varying heating rates have been investigated. The presented data reveal a significant displacement of glow peaks to higher temperatures as the heating rate increases, accompanied by variations in the height of the TL peaks. When the glow curve plot represents the TL intensity in counts/K against temperature (K), there is a noticeable shift towards higher temperatures with increasing heating rate. The activation energy (E) calculated using the two different heating rate methods is 1.08±0.7 eV. The ln(T2M/β) graph versus 1/kTM yields an activation energy value of E = 1.15±0.1 eV. This result agrees with data from the existing literature supporting the observed thermoluminescent behaviour of nano α-Al2O3 (40 nm) at different heating rates. The TL response and luminescence efficiency are examined in relation to changes in heating rate, revealing insights into thermal quenching phenomena. Additionally, activation energy calculations based on different heating rates are explored to understand the underlying mechanisms influencing TL behavior.